Think! new syllabus mathematics workbook 3 for grade 8 - Nautilus ,shell (Karachi: Oxford university press, 2024)
The Think New Syllabus Mathematics Workbook 3 for Grade 8 is designed to support students in mastering core mathematical concepts based on the new syllabus. It covers topics such as algebra, geometry, trigonometry, statistics, and probability with a variety of exercises that promote understanding and application. The workbook focuses on problem-solving skills and critical thinking, providing step-by-step explanations, practice questions, and real-world examples. Each chapter includes guided examples, followed by independent practice problems to reinforce learning. Additionally, it aligns with the curriculum requirements, making it a useful resource for both classroom learning and exam preparation.